2019
DOI: 10.3390/d11090159
|View full text |Cite
|
Sign up to set email alerts
|

Activity Patterns of Cave-Dwelling Bat Species during Pre-Hibernation Swarming and Post-Hibernation Emergence in the Central Appalachians

Abstract: In North America, bat research efforts largely have focused on summer maternity colonies and winter hibernacula, leaving the immediate pre- and post-hibernation ecology for many species unstudied. Understanding these patterns and processes is critical for addressing potential additive impacts to White-nose Syndrome (WNS)-affected bats, as autumn is a time of vital weight gain and fat resources are largely depleted in early spring in surviving individuals. Our study sought to examine autumn and spring bat activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
2
1
0
Order By: Relevance
“…These results are consistent with unfavorable conditions delaying juvenile development due to maternal use of torpor (e.g., Burles et al, 2009;Racey & Swift, 1981). Despite reproductive delays, we did not acoustically detect little brown bats later than early October, consistent with hibernation in Alberta beginning in mid-to late September (Schowalter et al, 1979), approximately one month earlier than in more southern locations (e.g., Humphrey & Cope, 1976;Muthersbaugh et al, 2019). The challenges of successfully reproducing in a short season are apparent in our estimated reproductive rate of 30%, which is among the lowest values in the literature (e.g., Barclay et al, 2004;Frick et al, 2010;Loeb et al, 2014) and is in stark contrast to southern locations where rates consistently approach 100% (e.g., Humphrey & Cope, 1976;O'Farrell & Studier, 1975).…”
Section: Phenology and Reproductionsupporting
confidence: 86%
“…These results are consistent with unfavorable conditions delaying juvenile development due to maternal use of torpor (e.g., Burles et al, 2009;Racey & Swift, 1981). Despite reproductive delays, we did not acoustically detect little brown bats later than early October, consistent with hibernation in Alberta beginning in mid-to late September (Schowalter et al, 1979), approximately one month earlier than in more southern locations (e.g., Humphrey & Cope, 1976;Muthersbaugh et al, 2019). The challenges of successfully reproducing in a short season are apparent in our estimated reproductive rate of 30%, which is among the lowest values in the literature (e.g., Barclay et al, 2004;Frick et al, 2010;Loeb et al, 2014) and is in stark contrast to southern locations where rates consistently approach 100% (e.g., Humphrey & Cope, 1976;O'Farrell & Studier, 1975).…”
Section: Phenology and Reproductionsupporting
confidence: 86%
“…However, other acoustic studies have documented a similar lack of relationship between basal area and bat detection (Hein et al 2009), and other fine-scale vegetation measurements may be more appropriate (Ford et al 2005). Precipitation often can have a negative impact on nightly bat activity and detection (Erickson and West 2002, Yates and Muzika 2006, Muthersbaugh et al 2019b), yet we generally found no effect. Bats are known to forage in light rain (Erkert 1982) and only delayed emergence minimally when rain noises were played outside roosts (Geipel et al 2019).…”
Section: Discussionsupporting
confidence: 47%
“…During the swarm, bats are thought to evaluate potential hibernacula while spending the day in roosts such as trees, buildings, and rock crevices outside of hibernacula [19,20]. Although swarming is well-known to include a noticeable increase in activity at hibernacula [21], little is known about the roosts used by bats during this time. This knowledge gap may hinder management of seasonally important habitats, a matter of increasing importance as species receive protected conservation status.…”
Section: Introductionmentioning
confidence: 99%